How Did Proposed Changes in the New Fair Labor and Standards Act Impact Collegiate Athletics Departments? - Nels Popp; Anita Moorman (University of Kansas Libraries, 2018)
In 2015, the Department of Labor introduced proposed changes to the Fair Labor Standards Act (FLSA) which significantly raised the minimum annual salary required for exempt employees. This proposed legislation had the potential to greatly impact college athletics departments, which traditionally have many employees who work long hours for relatively low salaries. The legislation was halted just days before its effective date. Many universities, however, went forward with changes in order to comply with the potential new law. The purpose of the current study was to determine how many athletic departments were affected by the changes, what types of changes were actually implemented, and how employees viewed the fairness of how resources are being distributed at their institution. Research revealed roughly half of all schools implemented some sort of change as a result of the proposed law, with 67.5% of those schools reporting an increase in salaries for some staff. Measures of distributive justice indicated low levels of perceived fairness in the allocation of salary across all NCAA Divisions, with employees at schools that did not make changes reporting significantly lower levels of perceived fairness. In addition, athletics directors reported statistically significant higher levels of perceived fairness in salary allocation than other staff members.